Implementation of the Voting Rights of Persons with Disabilities in the 2024 General Election in Koroha Village, District. Kodeoha, Kab. North Kolaka - Sopiandy, Dede; Murdiansyah, Eko Bambang; Ramly, Amisbah; Salim, Iksan Agus (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The purpose of this research is to identify the obstacles faced by persons with disabilities in exercising their voting rights, evaluate the efforts that have been made to improve the accessibility and inclusion of persons with disabilities in the electoral process, and provide policy recommendations that can improve accessibility and protection of the rights of persons with disabilities in general elections. Researchers use a type of research in the form of qualitative research which is more concerned with forming substantive based on concepts that arise in empirical data. Researchers do not feel they know what they do not know, so the research design developed is always open to the possibility of various changes needed and flexible to the conditions in the field. This research uses interview, observation, and documentation techniques to obtain relevant data. The results of the research The implementation of voting for persons with disabilities in the village is quite good, with the efforts of local election organizers to facilitate accessibility needs. The participation of people with disabilities in the 2024 General Election in Koroha Village is quite high, showing an increase in their awareness and trust. What can be considered is increasing socialization, providing adequate accessibility facilities at all polling stations, and training for KPPS officers to be more sensitive to the needs of persons with disabilities. General elections as a means of popular sovereignty to elect members of the House of Representatives, members of the Regional Representatives Council, the President, and Vice President are a manifestation of the 1945 Constitution of the Republic of Indonesia (UUD NRI)